2011
DOI: 10.1055/s-0039-1698892
|View full text |Cite
|
Sign up to set email alerts
|

Tooth Sensitivity in Fluorotic Teeth

Abstract: Objectives:The aim of this study was to compare the demographic and clinical features of tooth sensitivity (TS) in subjects with and without fluorosis.Methods:A total of 2249 subjects (378 subjects with fluorosis and 1871 subjects without fluorosis) were examined for TS during a study period of one year and TS was determined in 122 subjects. The level of TS was evaluated on a visual analogue scale (VAS). The sensitivity evaluation was made by applying tactile and cold air stimuli. In teeth sensitive to any sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 36 publications
2
21
1
Order By: Relevance
“…[ 23 24 ] Furthermore, the resulting dentine exposure from enamel pitting has been documented as an etiological factor for dentine hypersensitivity. [ 25 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 23 24 ] Furthermore, the resulting dentine exposure from enamel pitting has been documented as an etiological factor for dentine hypersensitivity. [ 25 ]…”
Section: Introductionmentioning
confidence: 99%
“…Dental fluorosis is much described about changes of bond strength to enamel. Recently researches have revealed the dentin changes induced by fluorosis (Vieira, Hancock, Dumitriu, et al, 2006;Vieira, Hancock, Limeback, Schwartz, & Grynpas, 2003), and a increasing risk of DH meanwhile (Tonguc et al, 2011). It was reported that microtensile bond strength decreased with the severity of fluorosis (Waidyasekera, Nikaido, Weerasinghe, & Tagami, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…However, a high intake of fluoride during tooth formation has a reverse consequence and after eruption and during function, the fluorosed teeth with dentin exposure may show sensitivity. A study has shown that the subjects with fluorosis might suffer from tooth sensitivity more than those with normal dentition (Tonguc, Ozat, Sert, Sonmez, & Kirzioglu, 2011). High concentrations of fluoride reduced the mineralisation rate of the teeth and that dentin fluoride level was positively correlated with the size of the dentinal tubules (Vieira, Hancock, Dumitriu, Limeback, & Grynpas, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Patients who have changes in their dentinal structures such as amelogenesis imperfect [16], fluorosis [17] and hypoplasias [18], have also reported a higher propensity to present dentinal hypersensitivity. Studies in this area, enabling the development of increasingly accessible products, would also favor these patients, for whom even quality of life is affected.…”
Section: Discussionmentioning
confidence: 99%